Morphotype-based characterization of arbuscular mycorrhizal fungal communities in a restored tropical dry forest, Margarita island-Venezuela - Fajardo, Laurie; Lovera, Milagros; Arrindell, Pauline; Aguilar, Victor Hugo; Hasmy, Zamira; Cuenca, Gisela (Revista de Biología Tropical, 2015)
The mycorrhizal component of revegetated areas after ecological restoration or rehabilitation in arid and semiarid tropical areas has been scarcely assessed, particularly those made after mining disturbance. We evaluated and compared the presence of arbuscular mycorrhizal fungi of a small area of restored tropical dry forest destroyed by sand extraction, with a non-restored area of similar age, at the peninsula of Macanao, Margarita Island (Venezuela). Our study was undertaken in 2009, four years after planting, and the mycorrhizal status was evaluated in four restored plots (8 x 12.5 m) (two were previously treated with hydrogel (R2 and R2’), and two were left untreated (R1 and R1’), and four non-restored plots of similar size (NR1 and NR1’ with graminoid physiognomy with some scattered shrubs; and NR2 and NR2’, with a more species rich plant community). Apparently the restoration management promoted higher arbuscular mycorrhizal fungi (AMF) species richness and diversity, particularly in restored soils where the hydrogel was added (R2 treatment). Soil of the NR1 treatment (with a higher herbaceous component) showed the highest spore density, compared to samples of soils under the other treatments. Considering species composition, Claroideoglomus etunicatum and Rhizophagus intraradices were found in all treatments; besides, Diversispora spurca and Funneliformis geosporum were only found in non-restored plots, while members of the Gigasporaceae (a family associated with little disturbed sites) were commonly observed in the plots with restored soils. Mycorrhizal colonization was similar in the restored and non-restored areas, being a less sensitive indicator of the ecosystem recovery. The trend of higher richness and diversity of AMF in the restored plot with hydrogel suggests that this management strategy contributes to accelerate the natural regeneration in those ecosystems where water plays an essential role.